Meet Me Halfway: Will Photoperiodic Responses of Interpopulation Hybrids of the Brown Marmorated Stink Bug Halyomorpha halys (Hemiptera: Heteroptera: Pentatomidae) Promote or Constrain Subsequent Invasions? - Sergey Ya. Reznik; Natalia N. Karpun; Margarita Yu. Dolgovskaya; Aida Kh. Saulich; Dmitry L. Musolin (Diversity, 2022)
Biological invasions often result from multiple invasion events. In the case of several subsequent invasive episodes, ‘newcomers’ are usually poorly adapted to local environmental conditions in contrast to the representatives of the already-established invasive population of the same species. Therefore, the mode of inheritance of life-history features determining the survival and performance of interpopulation hybrids is an important component of invasiveness. We investigated the mode of inheritance of the photoperiodic response in the brown marmorated stink bug, Halyomorpha halys, by crossing between the native population of South Korea and the invasive population of the Black Sea coast of Russia. The aim of this study was to predict the overwintering potential of the progeny from possible crosses between representatives of the native and invasive populations. The pre-adult development time and the incidence of winter adult diapause in the progeny of the interpopulation crosses were close to the average of the values recorded in ‘pure’ (unmixed) crosses. Female and male genotypes were equally important in the determination of these characters. Such a mode of inheritance is most likely determined by a polygenic control and would only partially promote subsequent invasion events from the native South Asian range of H. halys into Europe.